2013
DOI: 10.1102/1470-7330.2013.0046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of multimodality imaging in radiotherapy treatment planning for rectal cancer

Abstract: Radiotherapy plays an important role in the treatment of rectal cancer. Three-dimensional conformal radiotherapy and intensity-modulated radiotherapy are mainstay techniques of radiotherapy for rectal cancer. However, the success of these techniques is heavily reliant on accurate target delineation and treatment planning. Computed tomography simulation is a cornerstone of rectal cancer radiotherapy, but there are limitations, such as poor soft-tissue contrast between pelvic structures and partial volume effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Several lines of evidence have established that PET/CT delineates smaller GTVs which practically approximate the true tumour. 13,16,26,28,43 A possible explanation for the larger PET/CT-CTV result from this study is likely related to the inclusion of proximal and/or metastatic lymph nodes missed on CT in the CTV. 28 Although both MRI findings are consistent with the literature, this present review found two studies that compared T2W-MRI with DW-MRI, whereas the earlier review reported three studies which compared MRI with CT and co-registered MRI-CT.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several lines of evidence have established that PET/CT delineates smaller GTVs which practically approximate the true tumour. 13,16,26,28,43 A possible explanation for the larger PET/CT-CTV result from this study is likely related to the inclusion of proximal and/or metastatic lymph nodes missed on CT in the CTV. 28 Although both MRI findings are consistent with the literature, this present review found two studies that compared T2W-MRI with DW-MRI, whereas the earlier review reported three studies which compared MRI with CT and co-registered MRI-CT.…”
Section: Discussionmentioning
confidence: 83%
“…12 Currently, the mainstay of radiotherapy delivery technique for rectal cancer has been based on 3D conformal radiotherapy and advanced conformal techniques, namely, intensity-modulated radiotherapy (IMRT), volumetric-modulated arc therapy and imageguided radiotherapy (IGRT). 13 The advent of these techniques has demonstrated beneficial therapeutic ratio effects by maximising dose to the TV, reducing radiation toxicity to organs at risk (OAR), increasing the chance of local tumour control, and consequently, improving the quality of life. 14 However, the success of these techniques requires excellent imaging quality for accurate visualisation and delineation of the TV and OAR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate coverage of tumor volumes can be markedly improved with the use of PET and MRI (7,22). Prospective planning studies utilizing pre-treatment PET and MRI have led to changes in shape and size of GTVs in up to 72% of treatment plans and have identified new lesions in 15% of patients often leading to a change in treatment strategy (7,22).…”
Section: Discussionmentioning
confidence: 99%
“…As a mobile organ, non-rigid registration between PET/CT and MRI shows good results, but this must be considered for the treatment planning ( 83 ). FDG PET/CT adds therefore information to MRI, with potentially a larger GTV in total when using the union of MRI and PET, and new or differently evaluated lesions in as many as 15% of the patients, potentially changing the treatment ( 84 ); further studies are necessary to well define the place of FDG PET in this indication ( 85 , 86 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%